2021
DOI: 10.1021/acs.inorgchem.1c02771
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Picture of the Excited State Dynamics of Cu(I)- and Ru(II)-Based Photosensitizers with Long-Lived Triplet States

Abstract: Ru­(II)- and Cu­(I)-based photosensitizers featuring the recently developed biipo ligand (16H-benzo-[4′,5′]-isoquinolino-[2′,1′,:1,2]-imidazo-[4,5-f]-[1,10]-phenanthrolin-16-one) were comprehensively investigated by X-ray crystallography, electrochemistry, and especially several time-resolved spectroscopic methods covering all time scales from femto- to milliseconds. The analysis of the experimental results is supported by density functional theory (DFT) calculations. The biipo ligand consists of a coordinatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 93 publications
(222 reference statements)
7
27
1
Order By: Relevance
“…Although the choice of the metal center is important, the proper selection and optimization of the surrounding ligands are crucial. ,, In this regard, we and others have found that particularly large diimine ligands with an extended π-system in their backbone can provide beneficial properties. Consequently, several recent studies report on the successful application of 16 H -benzo-[4′,5′]-isoquinolino-[2′,1′:1,2]-imidazo-[4,5- f ]-[1,10]-phenanthrolin-16-one ( biipo ), a fully conjugated and planar phenanthroline-based ligand (see Figure ). As a key feature of biipo , an imide unit is directly fused to the 1,10-phenanthroline core. When coordinated to a photoactive metal center (see Figure ), this ligand forms a bichromophoric system consisting of a metal–phenanthroline unit and the fused naphthalimide unit.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the choice of the metal center is important, the proper selection and optimization of the surrounding ligands are crucial. ,, In this regard, we and others have found that particularly large diimine ligands with an extended π-system in their backbone can provide beneficial properties. Consequently, several recent studies report on the successful application of 16 H -benzo-[4′,5′]-isoquinolino-[2′,1′:1,2]-imidazo-[4,5- f ]-[1,10]-phenanthrolin-16-one ( biipo ), a fully conjugated and planar phenanthroline-based ligand (see Figure ). As a key feature of biipo , an imide unit is directly fused to the 1,10-phenanthroline core. When coordinated to a photoactive metal center (see Figure ), this ligand forms a bichromophoric system consisting of a metal–phenanthroline unit and the fused naphthalimide unit.…”
Section: Introductionmentioning
confidence: 99%
“…The naphthalimide unit, as an organic chromophore, exhibits a long-lived and nonemissive excited triplet state ( 3 LC), which is reached only with a low quantum yield due to the absence of heavy atoms. , However, the functional interaction between the metal–phenanthroline part of the resulting complexes and the naphthalimide moiety can circumvent this bottleneck, combining the advantages of purely organic and transition-metal-based chromophores. ,,,, In these complexes, the absorption of a visible photon causes a transition to an electronically excited singlet state, which can then relax into a ligand-centered 3 LC state. ,,, This relaxation often involves a triplet metal-to-ligand charge-transfer state ( 3 MLCT). A fast population of the 3 LC state of biipo was demonstrated for a corresponding Ru­(II) and a Re­(I) complex (see Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations